Using word splash strategy to teach the eighth grade students` reading comprehension - Ira Kusuma Wardani; Yentri Anggeraini; Neti Lastri (JOLE (Journal of Language Education), 2023)
The objective of this study was to find out the effectiveness of teaching reading comprehension by using the word splash strategy for junior high school students. The design used in this study was pre-experimental. The total population of this study was 197 students from seven classes, the writer used cluster random samples . The instrument in this study is multiple choice of reading comprehension test. Based on the results of the Pre-Test, the mean score of the Pre-Test was 58.52. The results of the Post-Test the mean score of Post-Test was 76.30. Based on statistical analysis, the writer found that the value of Sig.=0.000 less than the value of significance level (a=0.05 and Df=26). This shows that the alternative hypothesis was accepted, it means that the use of word splash strategy significantly increase junior high school reading comprehension.